DIAGNOSTICS OF THE EFFICIENCY OF MARKETING RESEARCH IN AN ANTI-CRISIS MANAGEMENT SYSTEM - LARKA, LUDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The main methodological approaches to determining the effectiveness of marketing research in the anti-crisis marketing system are shown. It was determined that, depending on the stage of development of the crisis situation, the diagnosis of the effectiveness of marketing research should take place within the limits of preventive, crisis and post-crisis marketing systems. Diagnostics of the effectiveness of marketing research should take place in quantitative and qualitative dimensions. It is clarified that when evaluating the effectiveness of marketing research, it is necessary to correlate the increase in the company’s profit as a result of conducting marketing research to the marketing budget of this research. The main goals of marketing research are systematized depending on the stage of development of the crisis situation in order to determine the effectiveness of marketing research in a qualitative dimension. It was determined that an alternative qualitative indicator of the effectiveness of marketing research can be an integral indicator that accumulates indicators of the effectiveness of the implementation of the main stages of marketing research. The purpose of the article is to study and systematize the key indicators of the effectiveness of marketing research at certain stages of the development of a crisis situation, according to which the company implements the concepts of preventive, crisis and post-crisis marketing. In the system of crisis marketing, it is already about the survival of the enterprise, therefore the primary task is to use the marketing budget of the enterprise as efficiently as possible. Under such conditions, the main goals of marketing research cover the issue of determining existing market parameters, i.e., in crisis conditions, the need to conduct descriptive (descriptive) marketing research increases. The key task of post-crisis marketing is to consolidate the effect of crisis marketing measures; in this case, marketing research is devoted to monitoring the competitive environment of the enterprise and directions for improving its product, price, sales and communication policies.